Ultrasound-Guided Surgery for Carpal Tunnel Syndrome: A New Interventional Procedure - Petrover, David; Hakime, Antoine; Silvera, Jonathan; Richette, Pascal; Nizard, Rémy (Seminars in Interventional Radiology, 2018)
Carpal tunnel syndrome (CTS) may be treated surgically if medical treatment fails. The classical approach involves release of the flexor retinaculum by endoscopic or open surgery. Meta-analyses have shown that the risk of nerve injury may be higher with endoscopic treatment. The recent contribution of ultrasound to the diagnosis and therapeutic management of CTS opens new perspectives. Ultrasound-guided carpal tunnel release via a minimally invasive approach enables the whole operation to be performed as a percutaneous radiological procedure. The advantages are a smaller incision compared with classical techniques; great safety during the procedure by visualization of anatomic structures, particularly variations in the median nerve; and realization of the procedure under local anesthesia. These advantages lead to a reduction in postsurgical sequelae and more rapid resumption of daily activities and work. Dressings are removed by the third day postsurgery. Recent studies seem to confirm the medical, economic, and aesthetic benefits of this new approach.
Keywords: carpal tunnel syndrome; ultrasound-guided treatment; minimally invasive surgery; carpal tunnel release; interventional radiology; ultrasound-guided surgery